2017
DOI: 10.1126/scisignal.aam6291
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autophagy, NF-κB signaling, and cell viability by miR-124 in KRAS mutant mesenchymal-like NSCLC cells

Abstract: KRAS mutant non-small cell lung cancer (NSCLC) may be classified into epithelial or mesenchymal subtypes. Mesenchymal NSCLCs and associated “KM” cell lines are generally less responsive than their epithelial counterparts to inhibition of the RAS pathway; identifying alternative networks that promote mesenchymal NSCLC survival may lead to more effective treatments for this subtype. Non-coding microRNA (miRNA) signatures can stratify tumors into diverse molecular subtypes. By regulating numerous targets in cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Recent research indicates that circHIPK3 functions as a ceRNA to sequester multiple miRNAs [16,19,28], among which MIR124-3p is a well-known tumor suppressor and its regulation role in autophagy was recently being emphasized [29]. It has been reported that IL6R is regulated by circHIPK3-MIR124-3p axis [16].…”
Section: Circhipk3 Regulates Autophagy Viamir124-3p-stat3 Axis In Autmentioning
confidence: 99%
“…Recent research indicates that circHIPK3 functions as a ceRNA to sequester multiple miRNAs [16,19,28], among which MIR124-3p is a well-known tumor suppressor and its regulation role in autophagy was recently being emphasized [29]. It has been reported that IL6R is regulated by circHIPK3-MIR124-3p axis [16].…”
Section: Circhipk3 Regulates Autophagy Viamir124-3p-stat3 Axis In Autmentioning
confidence: 99%
“…For example, miR-9 affects autophagy by targeting the products of the essential autophagy-related (ATG) genes ATG5 [ 68 ] and Beclin1 [ 75 ], whereas miR-17 targets ATG7 [ 66 ], Beclin1 [ 64 ], and p62/SQSTM1 [ 70 ]. miR-124 targets Beclin1 [ 74 ] and p62/SQSTM1 [ 71 ]. Modulation of this set of miRNAs that we identified by in silico analysis (miR-9, miR-16, miR-17, miR-93, miR-101, miR-124, miR-128, miR-200, miR-429, and miR-497) thus appears to have a strong potential to concertedly mediate the effects of oxidative stress on both protein ubiquitination and autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been shown that miR-124-3p can suppress inflammatory responses in traumatic acute lung injuries and thereby ameliorate those injuries [11]. A previous study of non-small cell lung cancers indicated that miR-124 helped to regulate autophagy, NF-kappa signaling, and cell viability, and that suppression of p62 expression by miR-124 was correlated with the NF-kappa subunit, RELA/p65 [14]. In a study of retinal microglia cells, it was shown that miR-124 directly controls Rac1 expression; furthermore, that study also revealed a miR-124-dependent mechanism in which Rac1 activation-mediated reactive oxygen species production stimulated p65 NF-kappa phosphorylation and induced the release of TNF-alpha from retinal microglial cells [15].…”
Section: Introductionmentioning
confidence: 99%